Induced pluripotent stem cells derived from an autosomal dominant lateral temporal epilepsy (ADLTE) patient carrying S473L mutation in leucine-rich glioma inactivated 1 (LGI1) - Ghee Wan Tan; Takayuki Kondo; Nagahisa Murakami; Keiko Imamura; Takako Enami; Kayoko Tsukita; Ran Shibukawa; Misato Funayama; Riki Matsumoto; Akio Ikeda; Ryosuke Takahashi; Haruhisa Inoue (Stem Cell Research, 2017)
Autosomal dominant lateral temporal epilepsy (ADLTE) is an inherited epileptic syndrome, and it is associated with mutations of leucine-rich glioma inactivated 1 (LGI1) gene. The underlying mechanisms of ADLTE are still unknown, as human neurons are difficult to obtain as a research tool. Human induced pluripotent stem cells (iPSCs) allow the generation of patient-derived neuronal cells in a dish, and can be a promising tool to model ADLTE. Here, we report the establishment of human iPSCs from an ADLTE patient carrying LGI1 mutation (c.1418C>T, p.Ser473Leu).